Retrograde Robotic Radical Prostatectomy: Description of a New Technique and Early Perioperative Outcomes. (10th March 2014) - Vricella, Gino J.; Klaassen, Zachary; Terris, Martha K.; Madi, Rabii
Abstract : Objectives . This research was conducted to describe a novel technique for performing robotic-assisted laparoscopic prostatectomy (RALP) using a retrograde approach that mimics the classic open surgical technique. Methods . From June 2009 to March 2011, we performed 18 nonconsecutive RALPs using a novel retrograde approach. Patients were initially selected with D'Amico low to intermediate risk disease. Pre-, intra-, and postoperative data were analyzed in all patients. Results . All 18 patients had successful surgery without any intraoperative complications. Mean preoperative PSA was 6.0 ng/mL. Nine patients had biopsy Gleason score (GS) 6, seven patients had GS 7, and two patients had GS 8. Fourteen patients had clinical stage T1c and four patients had stage T2a. Mean operative time was 198 minutes, with a mean robotic console time of 168 minutes. Fifteen patients had T2 disease on the final pathology and three had T3 disease. With a median follow-up of 11 months, 10 patients had an undetectable PSA. Conclusions . Our early experience with retrograde robotic-assisted laparoscopic prostatectomy demonstrates the feasibility of this approach with early outcomes comparable to the contemporary antegrade approach. Long-term study with a greater number of patients will be necessary to fully evaluate the oncologic and functional outcomes using this technique.